(untitled) (Journal of Applied Oral Science, 2008)
The purpose of this study was to evaluate the prevalence of oral lesions in HIV-positive patients attending the Specialized Service for Infectious-contagious Diseases and Parasitoses of the Health Secretariat of the State of Pará (URE-DIPE/SESPA), in the city of Belém, PA, Brazil. A total of 79 HIV-positive patients (53 males and 26 females) were examined. Clinical and epidemiological evaluations were done by correlating the lesions with gender, race, chronological age, risk behavior and prevailing immune status (CD4+ cells count). Lesion location and the presence of associated factors, such as alcohol use, smoking and denture wearing, were quantified individually for each type of lesion using a diagnostic pattern based on the clinical aspects. Approximately 47% of the patients (n=37) presented some type of oral lesion. Candidiasis (28%) and periodontal disease (28%) were the most common, followed by cervical-facial lymphadenopathy (17.5%). Other lesions observed were hairy leukoplakia, melanin hyperpigmentation, ulcerative stomatitis (aphthous), herpes simplex, frictional keratosis and pyogenic granuloma. This analysis presented some relevance as to the statistical data. Concerning CD4+ cells, most lesions manifested with the reduction of the CD count. There were a larger number of HIV-positive female heterosexual patients. Alcohol and/or smoking were strongly associated with the occurrence of hairy leukoplakia in these patients. Candidiasis and periodontal disease were the most common oro-regional clinical manifestations in the patients.